HAMBATAN PEMANFAATAN PELAYANAN NIFAS DI WILAYAH KERJA PUSKESMAS X : STUDI KUALITATIF - Montessori, Yolanda; Haryanti, Yunida; Amartani, Rizki; Masan, Lea; Tri Kurniati, Paskalia (NHM PRESS, 2024)
Postpartum period is a critical period for a mother and newborn because long-term health risks occur in this period. Maternal and neonatal deaths mostly occur in the first week after delivery. On the other hand, the postpartum period is a time that is often missed when obtaining quality midwifery services, especially in low and middle income countries. The aim of this research is to determine the barriers to utilizing postpartum services in the Puskesmas X Work Area in 2023. This research is a qualitative research using a phenomenological approach. Five informants were interviewed semi-structuredly, consisting of 1 mother postpartum 1 month, 2 mothers postpartum 2 months, and 2 mothers postpartum 3 months who were selected using purposive sampling technique. Based on the results of the thematic analysis, postpartum mothers have low knowledge about postpartum visits, so awareness about making visits is also lacking. Apart from that, the length of time that must be taken to be checked at a health service facility, inadequate means of transportation to access health service facilities, and not having a supply of expressed breast milk when having to leave the baby at a health service facility are also factors preventing postpartum mothers from making postpartum visits. Apart from that, health workers have not been optimal in providing information regarding the national policy of postpartum visits 4 visits and health workers in the local area have not made home visits. So home visits can be a solution so that midwives can continue to provide education and support to postpartum mothers.